Community Cultural Approach Using Cultural Care Nursing in Preventing the Transmission of COVID-19 in Ternate City - Wasis Nugroho; Aminudin Muhammad,; Ramli Muhammad (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Cultural values in the community are formed from how they maintain life, this is important for providing health services for nursing professionals. The phenomenon of the COVID-19 virus has become a pandemic problem in society. Indonesia also experiences this problem thoroughly in all regions, and it has become a non-natural national disaster. Prevention efforts continue to be carried out in the community. The Cultural Care approach to nursing is a choice of theoretical ideas to help improve health in society for the better. A total of 40 participants are the people of the city of Ternate and have local cultural values. Data collection was carried out using a questionnaire checklist and interviews. The research findings were obtained from 30 participants (70%). These findings provide compatibility of community empowerment methods with the problems, needs, and challenges that exist in the area of the community empowerment activities. These findings also provide suggestions for empowering people who have regional cultural arrangements and wish to overcome their health problems.